2018
DOI: 10.1136/bcr-2018-226094
|View full text |Cite
|
Sign up to set email alerts
|

A near-fatal case of intussusception and ischaemic perforation of stomach in first-trimester pregnancy: eight years after laparoscopic Roux-en-Y gastric bypass

Abstract: The increasing demand and popularity of bariatric surgery are not only due to the ever-increasing obesity epidemic but to tackle obesity-related comorbidities like diabetes and hypertension. However, bariatric surgery is not free of complications. One rare complication is intussusception, jejuno-jejunal intussusception being the most common. Intussusception has been defined both in pregnant and in non-pregnant women as well as men. We describe the case of a 40-year-old woman in the first trimester of pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Abdominal CT is considered the most sensitive, reliable and useful way of diagnosing intussusception with a reported accuracy of 58-100% [10]. MRI abdomen/pelvis is recommended in pregnant women to limit radiation exposure [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal CT is considered the most sensitive, reliable and useful way of diagnosing intussusception with a reported accuracy of 58-100% [10]. MRI abdomen/pelvis is recommended in pregnant women to limit radiation exposure [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Most intussusceptions occur in antegrade fashion, however, with RYGB, the intussusception is more often retrograde in nature [1,4,11,12]. All three limbs of the Roux-en-Y anastomosis can be affected by intussusception, however in most cases published so far it has been the common channel that has invaginated through the jejuno-jejunostomy [5].…”
Section: Discussionmentioning
confidence: 99%
“…Doño et al reported a case where a patient presented with symptoms 32 years after undergoing open RYGB [ 11 ]. Bhadra et al reported symptoms emerging nine years after surgery, while Chys et al indicated a variation of 9-11 years between presentation and surgery [ 12 , 13 ]. Conversely, Michiels et al presented a case with a comparatively shorter gap of two years between surgery and symptom manifestation [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
“…Doño et al reported that the patient presented with worsening abdominal pain with pain radiation to the flank: 10/10 on the pain scale associated with nausea and constipation[11]. Bhadra et al's report showcased a patient with 10/10 worsening abdominal pain with nausea and episodes of frank blood vomiting[12]. According to Teixeira et al, the patient reported having nausea, vomiting, intermittent stomach pain, distension of the abdomen, and no feces or flatus[15].Machado et al reported a patient with symptoms of abdominal pain and nonbilious vomiting, whereas Facchiano et al reported a patient with abdominal pain, bilious vomiting, and fever…”
mentioning
confidence: 99%